A docência no curso de direito: questões pedagógicas e o olhar de estudantes sobre o bom professor - Aguiar, Moema Lima Pereira Masters (2023)
This research aims to understand how teaching is constituted in the Law course from a bibliographic study and the conception of students from a federal public university. It bases its discussions on a theoretical framework consisting of productions that consider critical discussions about teaching and pedagogy in higher education. The study is qualitative in nature, using bibliographic research to discuss studies and research that thematize teaching in the Law course, situating its characteristics, scenarios and pedagogical demands. It resorts to the application of an online questionnaire for field research with the research participants, final year students of the Law undergraduate course at a federal public university, in order to identify perceptions regarding the teacher who is recognized as a good professor in his pedagogical action in this context. For data interpretation, it uses the content analysis technique and presents, as an educational product of the investigation, an e-book on teaching and pedagogical issues in the teaching and learning processes in the Law course. As main results, the research points out the following considerationssyntheses: the debate with academic studies on teaching in higher education highlights the complexity and specificities of the teaching profession in higher education, as well as the need for investment by Higher Education Educational Institutions in the stimulation and participatory mobilization of professors in continuous pedagogical training processes; the conceptions of the students, participants of the study, indicate that the teachers, who work in the Law course, are professionals who have vast legal knowledge, which is fundamental for the students, however it is also indicated by this public that their teachers need knowledge in the didactic-pedagogical perspective; the analyses of this study affirm the contributions of Pedagogy and Didactics as areas of knowledge, which can subsidize the formulation of continuous training processes for higher education teachers, collaborating to the formulation of possibilities and to overcome the challenges and dilemmas of teaching experienced in this context.